Plasmodium ovale in Indonesia. - Baird, J; Purnomo; Masbar, S (1990)
We report 34 infections by Plasmodium ovale found among 15,806 blood film examinations taken between 1973 and 1989 from several sites in Indonesia. Twenty five of the P. ovale infections occurred in a single sample of 514 people living in Owi, Irian Jaya. We detected five additional infections at 3 other sites in Irian Jaya. Other infections by P. ovale occurred at two sites in West Flores. Another infection has already been reported from East Timor. Despite relatively frequent sampling of populations on Sumatra, Kalimantan, Java and Sulawesi, P. ovale has not been found on those islands. It appears that this parasite occurs only on the easternmost islands of the Indonesian archipelago where it is nonetheless a rare finding.